Faulting, fault sealing and fluid flow in hydrocarbon reservoirs - Jones, G.; Fisher, Q. J.; Knipe, R. J. 1952- (Geological Society, 1998)
"Compared with many other areas of the petroleum geosciences, studies of the structural controls on fluid flow in hydrocarbon reservoirs are in their infancy. As hydrocarbon reserves have become depleted and the oil industry has become more competitive, the need to cut costs by optimizing production and predicting the occurrence of subtle traps has highlighted the importance of information on the way in which faults and fractures affect fluid flow. Structural geologists are now having to provide answers to questions such as: Are hydrocarbons likely to have migrated into (or out of) the trap? What is the likely height of hydrocarbons that a fault can support? Is it likely that compartments which have not been produced exist within a field and will therefore require further drilling?" "This volume aims to find answers to these questions."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.
Keywords: Faults (Geology); Hydrocarbon reservoirs.; Fluid dynamics.; Petroleum -- Geology.; elektronické knihy; electronic books